(untitled) (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: This study aimed to evaluate the prevalence, abundance, and identification of genera of gastrointestinal parasites in buffaloes belonging to an establishment in Villa Oliva, Ñeembucú Department, Paraguay. Materials and Methods: A total of 117 buffaloes were included in the study and divided into three groups of 39 (n = 39) animals—Group 1: = <12 months (G1); Group 2: = ><36 months (G2); and Group 3: >37 months (G3). All samples were tested using the saturated salt flotation. Eggs and oocyte counts were determined using McMaster’s method. Recuperation of larvae 3 was carried out after coproculture using the Baerman technique. Identification was based on morphological identification keys. Results: The presence of eggs and/or oocysts of parasites belonging to Cestoda, Protozoa, and Nematoda was noted. The prevalence of gastrointestinal nematode (GIN) was 36.75%. The highest abundance was observed in G1. After coproculture Moniezia expanza, Eimeria spp., and Haemonchus spp.; Teladorsagia spp./Ostertagia spp. were also identified. It is also observed that the incidence of nematode parasite infestation in female buffalo is high compared to males; however, in terms of microparasites, it is the opposite. According to our results, as buffalo age increased, parasite loads decreased considerably. Conclusion: Those results may link factors between hosts and the environment with the ability to maintain gastrointestinal infestation at levels that do not compromise health and body conditions. This study presented results of the prevalence, abundance, and identification of GINs from buffalos of Paraguay for the first time. J. Adv. Vet. Anim. Res., 11(4): 961–966, December 2024 http://doi.org/10.5455/javar.2024.k846